BET inhibitors down-regulate the expression of the essential lncRNA SMILO in multiple myeloma through regulation of the transcription factor FLI1 - Nahia Gómez-Echarte; Edurne San José-Enériz; Arantxa Carrasco-León; Naroa Barrena; Estibaliz Miranda; Leire Garate; Beatriz García-Torre; Sandra Alonso-Moreno; Naroa Gimenez-Camino; Estibaliz Urizar-Compains; Danel Olaverri-Mendizabal; Paula Aguirre-Ruiz; et al. (Haematologica)
Not available.